(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Adolescent reproductive health care is a current issue of great concern in Vietnam. Adolescents need to be provided the knowledge of reproductive health to help them understand and be aware of reproductive health risks, prevent and take care of their own health. Objective: Describe the current state of knowledge, attitude, and practice of adolescent reproductive health care of pupils at Tien Hung High School, Dong Hung district, Thai Binh in 2023. Methods: Cross-sectional study. The research collected information from 306 pupils at high school through questionnaires. Data were entered by Epidata 3.1 software and analyzed by SPSS 14.0 software. Results: The study results show that pupils’ general knowledge about adolescent reproductive health was 52.5%, with a difference in knowledge between male and female pupils (p<0,05). The general attitude of pupils about adolescent reproductive health was 74.9%. The general practice of pupils about adolescent reproductive health was 68.7%, the difference in attitudes and practices between males and females was not statistically significant (p>0.05). Conclusion: Families and schools need to increase support, share and organize learning programs about adolescent reproductive health for pupils.